2012
DOI: 10.1021/ol203251s
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Oxidative C–H Alkenylations of Anilides and Benzamides in Water

Abstract: A cationic ruthenium(II) complex enabled efficient oxidative alkenylations of anilides in water as a green solvent and proved applicable to double C-H bond functionalizations of (hetero)aromatic amides with ample scope. Detailed studies provided strong support for a change of ruthenation mechanism in the two transformations, with an irreversible metalation as the key step in cross-dehydrogenative alkenylations of benzamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(83 citation statements)
references
References 48 publications
2
81
0
Order By: Relevance
“…2 Apart from a variety of documented conventional methods, 3 isoindolinone can be readily prepared by the means of C-H activation. Our group, 4 the Lloyd-Jones/Booker-Milburn groups, 5 and the Wang group 6 recently revealed palladium-catalyzed sequences of C-H olefination/annulation to generate 3-monosubstituted isoindolinones; the Li group, 7 the Glorius group 8 and the Ackermann group 9 also disclosed a similar process but accomplished by rhodium or ruthenium catalysis. Regarding the broadly structural diversity of isoindolinones, it is clear that it will continue to remain an area of active investigations.…”
Section: Introductionmentioning
confidence: 90%
“…2 Apart from a variety of documented conventional methods, 3 isoindolinone can be readily prepared by the means of C-H activation. Our group, 4 the Lloyd-Jones/Booker-Milburn groups, 5 and the Wang group 6 recently revealed palladium-catalyzed sequences of C-H olefination/annulation to generate 3-monosubstituted isoindolinones; the Li group, 7 the Glorius group 8 and the Ackermann group 9 also disclosed a similar process but accomplished by rhodium or ruthenium catalysis. Regarding the broadly structural diversity of isoindolinones, it is clear that it will continue to remain an area of active investigations.…”
Section: Introductionmentioning
confidence: 90%
“…For instance, in medicinal chemistry they play a pivotal role affording chemically stable compounds as prodrugs with improved pharmacological profile, and many N-acylated derivatives are in clinical use. 3 On the other hand, acetanilides have natural aptitude to act as ortho directing group in C−H transformations to C−C bond formation, wherein functionalized benzophenone, 4 quinone, 5 bisphenyl, 6 or styrene 7,8 derivatives can be obtained by Pd or Rh catalysis, Figure 1. Besides, the reactivity of some ortho functional group of acetanilides is modulated by the presence of the N-acetyl moiety, which is thus selectively converted to more complex compound, constituting this kind of acetanilide into important synthetic intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, a search in the literature revealed that when other substituted acetanilides are needed as starting material in the context of a research project, the preparation used is very similar to that of parent acentanilide, which is almost the same of one century ago, which uses large amounts of solvents and additives such as acetic acid and sodium acetate, for instance. [5][6][7][8][9][10][11][12][13][14][15][19][20][21][22][23][24] It should be pointed out that, although there are a few syntheses of acetanilides in the absence of solvent, it is always necessary the use of grinding or microwave heating in these previously described syntheses or, more recurrent, the use of catalyst such as morpholinium bisulfate, zirconyl triflate, tris(pentaflurophenyl)borate, anatase phase TiO 2 nanoparticles, or even the unconventional rice husk ash, Figure 2. 24 Despite that solvent-free catalyst's dependent approaches represent important contribution, more environmentally friendly procedures which reduce the use of chemicals and energy is still needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pre- 20 functionalization of the starting materials in this protocol limited its application. More recently, combination of selective, catalytic activation of C-H bonds with functionalization to form C-S bonds has been a subject of particular interest in recent years.Various catalytic systems based on copper, 11 palladium, 12-15 ruthenium [16][17][18][19][20][21][22][23][24][25] 19 and rhodium 17- …”
mentioning
confidence: 99%